Exosomal circRNAs as promising liquid biopsy biomarkers for glioma - Wu, Xiaoke; Shi, Mengmeng; Lian, Yajun; Zhang, Haifeng (Frontiers in Immunology, 2023)
Liquid biopsy strategies enable the noninvasive detection of changes in the levels of circulating biomarkers in body fluid samples, providing an opportunity to diagnose, dynamically monitor, and treat a range of diseases, including cancers. Glioma is among the most common forms of intracranial malignancy, and affected patients exhibit poor prognostic outcomes. As such, diagnosing and treating this disease in its early stages is critical for optimal patient outcomes. Exosomal circular RNAs (circRNAs) are involved in both the onset and progression of glioma. Both the roles of exosomes and methods for their detection have received much attention in recent years and the detection of exosomal circRNAs by liquid biopsy has significant potential for monitoring dynamic changes in glioma. The present review provides an overview of the circulating liquid biopsy biomarkers associated with this cancer type and the potential application of exosomal circRNAs as tools to guide the diagnosis, treatment, and prognostic evaluation of glioma patients during disease progression.